Double-Voicing the Canadian Short Story - Kruk, Laurie, 1962- (Book collections on Project MUSE., 2016)
"Double-Voicing the Canadian Short Story is a comparative study of eight nationally and internationally-acclaimed Canadian short story writers in English: Sandra Birdsell, Timothy Findley, Jack Hodgins, Thomas King, Alistair MacLeod, Olive Senior, Carol Shields and Guy Vanderhaeghe. It addresses an important gap in contemporary Canadian literary criticism by focusing specifically on their short fiction. This book is the first work to address this cohort of authors in textual dialogue with one another. Drawing on narratological and formalist theory, including an interpretation of Bakhtin's important discussion of the "dialogical" nature of fiction, the author examines the multiple ways and means whereby this "double-voicing" manifests itself in the authors' stories. In the broadest sense, it operates at the level of theme, in representational or philosophical ironizing of dominant societal discourses and hegemonic values. This then opens up the question of who speaks--how is the "vision" conveyed by the "voice" of the story?--which the author terms thematics of focalization. This choice shapes the literary mode, or style, of the story, including the "double-voicing" created through irony, satire and parody. Finally, at the discursive or linguistic level, "double-voicing" appears in terms of the dialogizing of language itself. Neither programmatic nor reductive, the author's approach offers a thoughtful juxtaposition of select stories on themes of gender, mothers and sons, family storytelling, marriage, sexuality, and (the politics of) identity in order to show their distinctive "double-voicing" of these issues and relationships. As a multi-author study, its scope is broad and its readings valuable to Canadian literature as a whole, making the book of interest to students of Canadian literature or the short story, and to readers of both."--